Alcohol use disorders and ADHD. (September 2021) - Luderer, Mathias; Ramos Quiroga, Josep Antoni; Faraone, Stephen V.; Zhang-James, Yanli; Reif, Andreas
Highlights: ADHD and alcohol use / alcohol use disorder (AUD) share common genetic, neurobiological and neuropsychological associations. ADHD symptoms and alcohol use during adolescence mutually increase the severity of the other leading to an increased risk for ADHD and AUD. Thus, ADHD is highly prevalent in patients with AUD, and leads to worse treatment outcome. Routine screening for ADHD in AUD is highly recommended and the diagnostic process should start as early as possible. ADHD treatment includes long-acting stimulants, atomoxetine or guanfacine; psycho- and pharmacotherapy are indicated for both disorders. Abstract: Despite a growing literature on the complex bidirectional relationship of ADHD and substance use, reviews specifically focusing on alcohol are scarce. ADHD and AUD show a significant genetic overlap, including genes involved in gluatamatergic and catecholaminergic neurotransmission. ADHD drives risky behavior and negative experiences throughout the lifespan that subsequently enhance a genetically increased risk for Alcohol Use Disorders (AUD). Impulsive decisions and a maladaptive reward system make individuals with ADHD vulnerable for alcohol use and up to 43 % develop an AUD; in adults with AUD, ADHD occurs in about 20 %, but is vastly under-recognized and under-treated. Thus, routine screening and treatment procedures need to be implemented in AUD treatment. Long-acting stimulants or non-stimulants can be used to treat ADHD in individuals with AUD. However, it is crucial to combine medical treatment for ADHD with pharmacotherapy and psychotherapy for AUD, and other comorbid disorders. Identification of individuals at risk for AUD, especially those with ADHD and conduct disorder or oppositional defiant disorder, is a key factor to prevent negative outcomes.